2017
DOI: 10.1002/ijc.30617
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of lymph node‐DTCs in patients with node‐negative HNSCC

Abstract: This study was performed to systematically assess the prevalence, topography and prognostic impact of disseminated tumor cells (DTCs) in lymph nodes (LN) of patients with primary, regional and distant metastasis-free head and neck squamous cell carcinoma (HNSCC) who underwent resection with elective neck dissection. From the routinely processed resection specimen, we could prospectively analyze a total of 1.137 exactly mapped LNs of 50 pN0-HNSCC patients, classified as tumor free by routine histopathology. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…To address this, we stained patient samples for NR2F1 in normal adjacent epithelium, primary tumors, and lymph nodes that were confirmed to have solitary HNSCC DTCs but not over metastasis [21]. Pancytokeratin was used as a marker to identify cells of epithelial origin in all tissues [22]. Cells were scored as NR2F1 hi , NR2F1 med , or NR2F1 −/low .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this, we stained patient samples for NR2F1 in normal adjacent epithelium, primary tumors, and lymph nodes that were confirmed to have solitary HNSCC DTCs but not over metastasis [21]. Pancytokeratin was used as a marker to identify cells of epithelial origin in all tissues [22]. Cells were scored as NR2F1 hi , NR2F1 med , or NR2F1 −/low .…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted February 2, 2021. ; https://doi.org/10.1101/2021.01.30.428967 doi: bioRxiv preprint nodes that were confirmed to have solitary HNSCC DTCs but not over metastasis [21]. Pancytokeratin was used as a marker to identify cells of epithelial origin in all tissues [22]. Cells were scored as NR2F1 hi , NR2F1 med , or NR2F1 -/low .…”
Section: C26 Treatment Suppresses Lung Metastasis By Activating An Nr2f1 Hi /P27 Hi /Ki67 Lo Dormancy Profile In Solitary Dtcsmentioning
confidence: 99%
“…According to the 6 th edition of International Union Against Cancer (UICC), lymph node metastasis (LNM) is classified into isolated tumor cells (ITC), micrometastasis (MI), and macrometastasis (MA), depending on the size of the metastatic deposit (5). Methods to investigate the presence of MI vary, from serial slices with hematoxylin and eosin (H&E) staining, immunohistochemical (IHC) staining, to real-time reverse transcription-polymerase chain reaction (RT-PCR) (6)(7)(8)(9). Cytokeratin is one component of the cytoskeleton of epithelial cells that is not present in normal lymph nodes, and its corresponding antibody is widely used to detect minute deposits of tumor cells in lymph nodes by IHC staining.…”
Section: Introductionmentioning
confidence: 99%
“…However, if we only pursue a higher survival rate, most patients will be regarded as 'overtreated'. At present, the technique for detecting occult metastatic lymph nodes in the neck is still imprecise; we can detect susceptible nodes only by physical examination, B-scan ultrasonography, and enhanced computed tomography (CT)/magnetic resonance imaging (MRI), but diagnoses obtained by these methods are far from precise [2,3]. Studies have shown that the rate of occult metastasis in the early stages of oral cancer is about 30% [1,4,5], meaning that nearly 70% of patients with negative nodes underwent neck dissection during routine treatment.…”
Section: Introductionmentioning
confidence: 99%